When do our patients need a pinch of salt - Saseedharan, Sanjith (Bangladesh Critical Care Journal, 2015)
Hyponatremia is a well known occurrence in traumatic and non traumatic brain injury which is known to complicate the management, affect the prognosis and increase hospital length of stay. Hypertonic saline is one of the drugs among the clinicians armamentarium in order to combat this complication. However its use is marked with many controversies and myths due to lack of robust evidence and non uniformity of trial protocols. In this review the author attempts to review the use of hypertonic saline in brain injury touching on practical use, indications, limitations and goes on to suggest a practical protocol for hypertonic saline in brain injury with raised intracranial pressure. Data Sources: MEDLINE, MICROMEDEX, The Cochrane database of Systematic Reviews from 1967 through May 2012. Bangladesh Crit Care J March 2015; 3 (1): 22-26